2021
DOI: 10.3390/ijms22115970
|View full text |Cite
|
Sign up to set email alerts
|

The PFKFB3 Inhibitor AZ67 Inhibits Angiogenesis Independently of Glycolysis Inhibition

Abstract: Angiogenesis is the process of new blood vessel formation. In this complex orchestrated growth, many factors are included. Lately, focus has shifted to endothelial cell metabolism, particularly to the PFKFB3 protein, a key regulatory enzyme of the glycolytic pathway. A variety of inhibitors of this important target have been studied, and a plethora of biological effects related to the process of angiogenesis have been reported. However, recent studies have disputed their mechanism of action, questioning whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…48 In a recent publication by Veseli et al, authors identified that AZ67 inhibitor is highly selective to PFKFB3, and inhibits the angiogenesis process independent of glycolysis inhibition. 49 In the present manuscript, we also identified similar findings, where we show that AZ67 has no effect on the expression of PFKP and PFKL, and on extracellular lactate production, unlike PFK15, thereby suggesting their independent mechanism of action in TNBC cells. However, our results also clearly demonstrate the ability of PFK15 to modulate PFK-1 F I G U R E 8 Schematic diagram of the proposed anticancer mechanism of combination treatment (PFK15 + siPFKL) in triplenegative breast cancers (TNBCs).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…48 In a recent publication by Veseli et al, authors identified that AZ67 inhibitor is highly selective to PFKFB3, and inhibits the angiogenesis process independent of glycolysis inhibition. 49 In the present manuscript, we also identified similar findings, where we show that AZ67 has no effect on the expression of PFKP and PFKL, and on extracellular lactate production, unlike PFK15, thereby suggesting their independent mechanism of action in TNBC cells. However, our results also clearly demonstrate the ability of PFK15 to modulate PFK-1 F I G U R E 8 Schematic diagram of the proposed anticancer mechanism of combination treatment (PFK15 + siPFKL) in triplenegative breast cancers (TNBCs).…”
Section: Discussionsupporting
confidence: 85%
“…Herein, we also like to discuss an ongoing debate among research fraternity over the specificity of 3PO inhibitors like PFK15, as it has been shown that PFK15 have much higher IC 50 toward PFKFB3 enzyme 48 . In a recent publication by Veseli et al, authors identified that AZ67 inhibitor is highly selective to PFKFB3, and inhibits the angiogenesis process independent of glycolysis inhibition 49 . In the present manuscript, we also identified similar findings, where we show that AZ67 has no effect on the expression of PFKP and PFKL, and on extracellular lactate production, unlike PFK15, thereby suggesting their independent mechanism of action in TNBC cells.…”
Section: Discussionmentioning
confidence: 98%
“…Second, a dose‐dependent effect of PFKFB3 inhibition might exist. Third, the PFKFB3 inhibitors may have “off‐target” effects, that have already been demonstrated (Emini Veseli et al, 2021; Wik et al, 2020). Further investigations are needed to verify these possibilities.…”
Section: Discussionmentioning
confidence: 87%
“…This involvement occurs by facilitating the expression of the pro-apoptotic transcription factor FOXO3A and its downstream genes, including p21, p27, and FAS [ 29 ]. Moreover, PFKFB3 has shown to promote pathological endothelial cell proliferation and vessel sprouting through filopodia/lamellipodia formation and directional migration [ 30 ]. Additionally, PFKFB3 activation has been linked to the impairment of endothelial barrier function within the tumor microenvironment by promoting VE-cadherin endocytosis in endothelial cells and reducing the adhesive properties of pericytes through downregulating N-cadherin expression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%